2018
DOI: 10.12688/wellcomeopenres.14241.1
|View full text |Cite
|
Sign up to set email alerts
|

The neural determinants of age-related changes in fluid intelligence: a pre-registered, longitudinal analysis in UK Biobank

Abstract: Background: Fluid intelligence declines with advancing age, starting in early adulthood. Within-subject declines in fluid intelligence are highly correlated with contemporaneous declines in the ability to live and function independently. To support healthy aging, the mechanisms underlying these declines need to be better understood. Methods: In this pre-registered analysis, we applied latent growth curve modelling to investigate the neural determinants of longitudinal changes in fluid intelligence across three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…In contradistinction, a positive association of the Fmn with the FI (Cam-CAN) has been reported by Kievit et al (2016). Even more complicated is the comparison with results of the UK Biobank study (Kievit et al, 2018) since the latent variable is defined with a set of measures that have been suggested to be difficult to interpret (Lyall et al, 2016). Even more complicated is the comparison with results of the UK Biobank study (Kievit et al, 2018) since the latent variable is defined with a set of measures that have been suggested to be difficult to interpret (Lyall et al, 2016).…”
Section: Mimic (Watershed) Model Of Integrated Wm and Cognitive Meamentioning
confidence: 91%
See 4 more Smart Citations
“…In contradistinction, a positive association of the Fmn with the FI (Cam-CAN) has been reported by Kievit et al (2016). Even more complicated is the comparison with results of the UK Biobank study (Kievit et al, 2018) since the latent variable is defined with a set of measures that have been suggested to be difficult to interpret (Lyall et al, 2016). Even more complicated is the comparison with results of the UK Biobank study (Kievit et al, 2018) since the latent variable is defined with a set of measures that have been suggested to be difficult to interpret (Lyall et al, 2016).…”
Section: Mimic (Watershed) Model Of Integrated Wm and Cognitive Meamentioning
confidence: 91%
“…Besides, findings from the same group (Kievit et al, 2018) showed a weak but significant negative association between age and fluid intelligence. As the authors state, the "suboptimal task design" restricted the exploration of cognitive interpretation.…”
mentioning
confidence: 83%
See 3 more Smart Citations